PENGARUH KEPEMIMPINAN TERHADAP SEMANGAT KERJA KARYAWAN - I Komang Oka Permadi; Made Pradnyan Permana Usadi (J-MIND (Jurnal Manajemen Indonesia), 2022)
A leader must be able to mix and govern current production components in order for the company to continue to exist. Because the firm's survival depends on employees who function as the driving force and carry out corporate tasks, a successful leader is one who understands his subordinates' wants and desires. The purpose of this study is to see how leadership affects employee morale at PT. Aditya Sinar Pratama Klungkung. Spearman rank correlation analysis, determination, and the t test were utilized as analytical techniques. The correlation r = 0.766, which is between 0.600 and 0.799, indicates that there is a positive correlation and a significant association between leadership and employee morale, implying that as leadership improves, so does employee morale, and vice versa. The coefficient of determination derived from the analysis of determination was 58.60 percent, indicating that leadership influenced employee morale by 58.60 percent, while the remaining 41.40 percent was influenced by other factors not investigated. The t-test calculation yielded t-count = 8.596, which indicates that t-count is higher than t-table. According to the test criteria, H0 is rejected whereas Hi is approved, indicating that leadership has an impact on employee morale, as evidenced by the significant value of 0.00 from a = 0.05.